Unusually Marked: A Cross-Linguistic Study of Foregrounding in Virginia Woolf’s “The Mark On The Wall” and its Albanian Translation - Qafzezi, Eriola (Vertimo studijos, 2025)
This paper investigates how foregrounding is realized in Virginia Woolf’s The Mark on the Wall and its Albanian version Njolla në Mur (translated by Elvana Zaimi). Adopting a comparative stylistic approach, the study examines deviations at the graphological/phonological, lexicogrammatical, and semantic levels, identifying how these stylistic effects are preserved, transformed, or neutralized in translation. Close reading, supported by selective corpus insights, reveals a clear hierarchy of translatability: graphological and phonological foregrounding is the most vulnerable to change, lexicogrammatical markedness is largely maintained, and semantic foregrounding, especially metaphors and figurative patterns, shows the highest degree of preservation. The findings reveal that Woolf’s modernist style is partially reshaped in Albanian, with the translator prioritizing semantic fidelity and syntactic rhythm over sound-based or punctuation-driven effects. By analyzing a less studied language pair, the study contributes to a broader understanding of how modernist stylistic innovation travels across linguistic and cultural contexts.